Go to sleep, anxiety! - Chi, Luna (Disney Press, 2024)
Based on the Disney/Pixar animated feature film Inside Out 2, releasing this summer in theaters, stories at various reading levels take kids on an all-new adventure inside the mind of now-teenager Riley, who is definitely feeling all kinds of new Emotions!